A MODEL OF MADRASAH BASED-MULTIPLE INTELLIGENCES (A study in Madrasah Pembangunan, Lab School of UIN Syarif Hidayatullah Jakarta) - Bahrissalim, Bahrissalim (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Developing madrasah is basically developing the excellence of human resource. Yet, today, unfortunately, there seems to be a lot of madrasahs hamper students’ intelligence to grow. Madrasah Pembangunan (MP) is a laboratory madrasah (lab school) of Faculty of Tarbiyah and Teaching Science UIN Syarif Hidayatullah Jakarta. To keep its excellence in the field of innovation, Madrasah Pembangunan integrates “multiple intelligences” into its education system. Madrasah based-multiple intelligence is sort of madrasah that appreciates various intelligence possessed by students. Regarding with its education system, the following are some of its implementations; Using “Multiple Intelligences Research” (MIR) as a students recruitment method, changing some indicators toward the excellence of the madrasah, teachers’ teaching and learning paradigm in the class, and learning evaluation model. MIR is a research method to identify the tendency of the most influenced and outstanding intelligence owned by students. Through MIR, students and teachers are informed various issues such as students’ intelligence tendency graphic, students’ learning style as well as recommended creative activities. Data resulted from MIR is used to develop learning process. To put it another way, the data is not used to decide whether students are accepted or not. Indicators of the best madrasah is a madrasah that concerns the quality of learning process “the best process” rather than the quality of input of its students. Besides, not only are teachers in this type of madrasah believed to be able to guarantee if students are led toward the right and better changes but also teachers in madrasah based multiple intelligences adopt such a paradigm that every single student is a star. Through this paradigm, all teachers are demanded to demonstrate their best effort to develop all of the student's intelligence through the implementation of learning based-multiple intelligence which is oriented to enhance all of the intelligence and to adjust teachers’ teaching style with students’ learning style. Authentic assessment adopts ipsative concept which means students learning progress is measured by the progress of students itself recognized through before and after getting learning materials. As its consequence, this assessment does not allow students to be compared with others.